The Effectiveness of Using Android-Based Interactive Learning Media Development Results With The Assistance of Smart Apps Creator (SAC) on Social Aritmatic Materials - Romdhoni, Mohammad Rifqi; Agustina, Eka Nurmala Sari; Ayuningtyas, Nurina (Universitas Wiralodra, 2023)
This study aims to: determine the effectiveness of the use of instructional media, and determine the practical effect of using instructional media on student learning outcomes. The research method used is descriptive quantitative which aims to describe the practicality of using learning media, the effectiveness of using learning media, and the effect of using learning media on student learning outcomes. The analysis technique used in this study to determine the effect of the practicality of using instructional media on student learning outcomes is simple linear regression analysis. The results showed that the practicality level of learning media was 80%, and the completeness level of students was 76%, so it can be concluded that the learning media developed met practical and effective criteria. The results showed that the assumptions of linear regression were met, namely the data were normally distributed, the data were homogeneous and there was no correlation between the data. So that a simple linear regression test can be carried out partially and the results obtained are tcount = 5.617 which is greater than the value ttable = 2.04841 which means H0 is rejected, so the practicality of using instructional media influences student learning outcomes.